V-shaped oxydiphthalimides: side-chain engineering regulates crystallisation-induced emission enhancement. Issue 3 (9th November 2016) - Gopan, Gopika; Salini, P. S.; Deb, Somadrita; Hariharan, Mahesh
Abstract : Side-chain engineering on V-shaped oxydiphthalimides (ODPs) resulted in a linear relationship between crystallisation-induced enhanced emission and the volume of the side-chains at the imidic position. Abstract : Tuning the luminescence properties of solid state materials by controlling the molecular packing in the crystal has played an important role in designing new functional materials. A series of five V-shaped oxydiphthalimides (ODPs) were synthesised. Side-chain engineering has been successfully utilized to systematically tune their luminescence properties in the crystalline state by introducing sterically bulky side-chains at the imidic nitrogen. Fluorescence spectroscopy and single crystal X-ray analyses disclose the effect of conformational twisting and bulkiness of imidic substituents on crystallisation-induced emission enhancement (CIEE). Detailed analysis revealed that the CIEE factor of ODPs shows a linear dependence on the percentage volume of the side-chain.